Modeling and simulation of single phase inverter with PWM using MATLAB/SIMULINK - Azuan, Alias (2007)
This project is about modeling and simulation of single phase Pulse Width Modulation (PWM) inverter. The model was implemented using MATLAB/Simulink with the SimPowerSystems Block Set. The Insulated Gate Bipolar Transistor (IGBT) model was used as switching device. This project is purposed to use MATLAB/Simulink software to design, analysis and evaluation of power electronic converter and their controllers. Besides, it can show what differential in simulation of this software with others. For modeling, Simulink provides a graphical user interface (GUI) for building model as block diagram, using click-and-drag mouse operation. Simulink includes a comprehensive block library of sink, sources, linear and nonlinear components and connectors. We also can customize and create our own block. After a model is defined, it can simulate, using a choice of integration methods, either from Simulink menus or by entering command in MATLAB’s command window. In addition, the parameter can be changed and immediately see what happen for ‘what if’ exploration. In inverter full bridge inverter circuit, an AC output is synthesized from a DC input by closing and opening the switches in appropriate sequence or switching scheme. For that, the Pulse Width Modulation technique is used in control the closing and opening switches. The switching scheme applied is unipolar. The PWM signal is used to control ON/OFF switching state of the IGBTs will functions in driver model that created to control the switching scheme. Then, the simulation is made from the inverter model in Simulink. The output voltage was obtained from Simulink and Pspice. At the end of this project, the results from simulation were compared between Simulink and Pspice.